2015
DOI: 10.14221/ajte.2015v40n1.7
|View full text |Cite
|
Sign up to set email alerts
|

Using Qualitative Research Methods to Assess the Degree of Fit between Teachers’ Reported Self-efficacy Beliefs and their Practical Knowledge during Teacher Education

Abstract: There is a need for qualitative research into teachers' selfefficacy beliefs so that the relationship between these beliefs and other cognitions possessed by teachers, including their practical knowledge, can be better understood by teacher educators. Teachers' self-efficacy beliefs may need supporting if they seem too low or challenging if they seem too high. However, clear criteria are needed to facilitate assessment, together with the use of rigorous qualitative methods. This article explores these issues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 71 publications
2
32
0
1
Order By: Relevance
“…While Karimi et al (2016) presented their findings in the form of descriptive statistics, in contrast, qualitative studies have provided 'thick description' (Geertz, 1973) of observed teaching practice related to developing practical knowledge and LTSE beliefs in specific areas (Wyatt, 2008(Wyatt, , 2010(Wyatt, , 2013(Wyatt, , 2015a. For example, focusing on how an English teacher developed in his use of group work to help low achievers, Wyatt (2010) explored growth in his LTSE beliefs in relation to developing practical knowledge with regard to "learners and learning, the curriculum, teaching techniques, the school context and his own sense of himself as a researcher of his own practice" (p. 603).…”
Section: Domain-specific Ltse Beliefs Studies Considering Classroom Pmentioning
confidence: 99%
See 3 more Smart Citations
“…While Karimi et al (2016) presented their findings in the form of descriptive statistics, in contrast, qualitative studies have provided 'thick description' (Geertz, 1973) of observed teaching practice related to developing practical knowledge and LTSE beliefs in specific areas (Wyatt, 2008(Wyatt, , 2010(Wyatt, , 2013(Wyatt, , 2015a. For example, focusing on how an English teacher developed in his use of group work to help low achievers, Wyatt (2010) explored growth in his LTSE beliefs in relation to developing practical knowledge with regard to "learners and learning, the curriculum, teaching techniques, the school context and his own sense of himself as a researcher of his own practice" (p. 603).…”
Section: Domain-specific Ltse Beliefs Studies Considering Classroom Pmentioning
confidence: 99%
“…For example, it is often overlooked that it can be deeply problematic if teachers are over-efficacious in relation to specific aspects of their work, since these teachers can then become relatively closed to learning (Wheatley, 2005;Wyatt, 2015a). In this light, it is interesting that in the studies of both Chacón (2005) and Karimi et al (2016), the most efficacious teachers were found to make the most clear-cut methodological choices: either for CLT or GTM in Chacón (2005); either for competence-or text-based approaches in Karimi et al (2016).…”
Section: Implications For Research and Teacher Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Asimismo, resulta necesario que se realicen más investigaciones en esta línea para lograr una mayor comprensión de la autoeficacia docente y poder mejorar la formación de los maestros en nuestro país. Este trabajo puede ser el punto de partida para futuras investigaciones de carácter longitudinal para que, como apunta, Wyatt (2015), se pueda explorar más profunda y ampliamente en sus creencias de autoeficacia. También sería interesante realizar investigaciones que analizaran las relaciones existentes entre la autoeficacia lingüística y metodológica en los docentes de inglés en Educación Primaria.…”
Section: Reflexiones Finalesunclassified